Analysis of Curriculum 2013 Reviewed From The Standard Process on The Physics Subject at SMA Yadika Natar - Aldeska, Jusi; Maharta, Nengah; Suana, Wayan (STKIP Santu Paulus Ruteng, 2018)
This research focuses on describing the standard process of 2013 curriculum implementation as well as the obstacles faced by the teachers in designing and executing the teaching-learning process of phyisics in tenth grade at SMA Yadika Natar. The descriptiver research was implemented as the design of this research. Furthermore, the resarch was held during the even semester in 2017/2108 academic year. During the research, lesson plan designed by the teachers and also the teaching-learning activities were analyzed to gain the data. The data, however, were gained by using observation, interview, and documentation. Moreover, the method used in this research were data reduction, data serving, and data verification. In short, the results were served in a form of lesson plan containing the scientific approach aspect which emphasizes the 2013 curriculum. Althogh, the teaching learning activity of the tenth grade at SMA Yadika Natar has facilitated the scientific approach and developed the students charracters. Yet, in the pre-activities, the activities are lacks of motivating session in which it should triger the students to get involved in were the teahcing learning activities. In addition, the teachers of SMA Yadika Natar find some obstacles in desigining lesson plan which will make them take more times. This could be appeared since the form at of 2013 curriculum slightly different with the school based curriculum (KTSP). Moreover, oganizing the class is still one of the teachers obstacles.